'Back to our Roots?' Re-visiting psychoanalytically-informed baby and young child observation in the education of student social workers. Issue 3 (2nd July 2016) - Hingley-Jones, Helen; Parkinson, Clare; Allain, Lucille
Abstract : While there is a well-established literature on psychoanalytically-informed baby and young child observation in social work education, little has been published recently. This paper reviews the rationale for its use, evaluating its impact on students' learning in the light of contemporary policy and practice contexts facing social work education. Analysis of feedback gained from a recent cohort, identifies three ways in which learning through baby and young child observation contributes: firstly, students encounter and learn about the complexity of child development from the direct experience of observing and secondly, observing facilitates the development of important skills for practice; students' 'use of self'. Thirdly, through observing, students describe how they develop the capacity to take-up and sustain a professional role. Well-structured teaching and learning through observation is therefore shown to provide a rigorous, theoretically-grounded contribution to the training of university-based social work students entering this complex and challenging professional field.